Starting out with Java from control structures through objects - Gaddis, Tony (Pearson, 2013)
In "Starting Out with Java: From Control Structures through Objects" , Gaddis covers procedural programming-control structures and methods-before introducing object-oriented programming. As with all Gaddis texts, clear and easy-to-read code listings, concise and practical real-world examples, and an abundance of exercises appear in every chapter.